FEATURES OF HUMORAL IMMUNITY INDICATORS IN THE BLOOD SERUM OF PATIENTS WITH ADENOVIRAL CONJUNCTIVITIS BEFORE AND AFTER TREATMENT - Guljamol R. Odilova; Nargiza Y. Khudiyeva (Central Asian Journal of Medicine, 2023)
Inflammatory eye diseases of viral, bacterial and mixed etiology are widespread and are a serious medical and social problem, accounting for more than 40% of all outpatients. The most common agents that cause damage to the organ of vision are adenoviruses (ADVs). Adenoviral eye damage occurs in 10-12% of all cases of adenoviral damage to the body. In addition, adenoviruses remain the most common causative agents of hospital ophthalmic infections. In addition to acute forms, adenoviral eye infection can also occur in the form of chronic and recurrent forms, the proportion of which is currently difficult to estimate.